Distribution and Characteristics of Organochlorine Pesticides in Soils from Conservation Areas of the Miyun Reservoir - Zhao, Zhijie; Zeng, Xiangfei; Liang Zhao; Jiao, Xiaolin; Qian Chen (Journal of Basic Science and EngineeringJournal of Basic Science and Engineering, 2020)
223 surface soil samples from conservation areas of the Miyun Reservoir were collected for detecting the concentration of organochlorine pesticides (OCPs) residues.The pollution characteristics,spatial distribution,influencing factors,origins of OCPs,and ecological risks were systematically explored.The results showed that the concentration of HCHs and DDTs in the soil samples ranged from ND to 2.10ng/g and ND to 526ng/g,respectively.The HCHs and DDTs in the Miyun reservoir presented zonal and discrete distribution characteristics,and the maximal values appeared in areas with dense population and developed agriculture.Moreover,both land use pattern and soil physical-chemical properties significantly impacted on the distribution of HCHs and DDTs.Highest concentration was found in farmland,and pH value was found to have greatest effect on the OCPs distribution.Furthermore,the OCPs residues in soils were mainly originated from the historical residues,atmospheric precipitation and recent inputs.Compared with other similar soil samples from different regions,the concentration of HCHs and DDTs in soil samples of the Miyun reservoir were at medium-low level,which suggested that HCHs and DDTs in the Miyun reservoir were in a state of low danger.以密云水库水源保护区为研究区域,对采集的223个表层土壤样品开展了有机氯农药残留浓度的测定,并对其污染特征、空间分布、影响因素、污染来源及生态风 险进行了探讨.结果表明,研究区域内HCHs和DDTs的总量变化范围分别在ND-2.10ng/g和ND-526ng/g之间,gamma-HCH、p ,p'-DDE和p,p'-DDT的检出率较高.HCHs和DDTs在空间上的分布呈现带状和离散性分布特征,浓度极值出现在人口密集和农业发达的地区. 土地利用方式和土壤理化性质均会对HCHs和DDTs的分布产生较大影响,其中耕地残留量最高,土壤pH值影响最大.HCHs和DDTs主要来源于早期残 留、大气的干湿沉降及近期的农药输入等.与国内外其他类似区域表层土壤相比,密云水库保护区土壤有机氯农药处于中等偏低水平,区域内总体生态风险较小,个 别点位可能存在潜在生态风险.